WOMEN ENTREPRENEURSHIP IN THE NEW NORMAL ERA: : A COMPARISON BETWEEN HYBRID AND PURE WOMEN ENTREPRENEURS - Siti Nur Azizah (LPSDI Bina Patria, 2023)
The aim of this article is to analyze and compare women's entrepreneurship by comparing motives, success factors, and problems in the business of hybrid women entrepreneurs and pure business women in the new normal era. The study included 40 female entrepreneurs who have businesses and 30 working women who have a business (hybrid women entrepreneurs) in Central Java, Indonesia. A quantitative method was used in this study to distribute questionnaires. The data were processed with the Wilcoxon test, to analyze and compare motivation factors, success factors, and entrepreneurial problems. Both women in business are motivated to earn income. Hybrid women entrepreneurs value the intrinsic rewards they get from their work, such as satisfaction and freedom. The study found that management skills and government support are more important factors for women’s entrepreneur success. They have stated that competition and undependable employees as their big problems in business. Government support in training and financial support are valuable in the new normal era to reach their destination.